Security threats to the Olympic Games - Lechner, Felix (Πανεπιστήμιο Πελοποννήσου, 2014)
Security at international mega events like the Olympic Games is an up to date topic in the media. For this reason this thesis looks at security threats at Olympic Events. The introductory literature research shows that not much research has been done on the topic in the last millennium. Only recently the interest of scholars in the topic rose rapidly, especially also after events like 9/11. Most of the publications are also made in direct context to specific Games and events, only little about security at the Olympics or at mega events in general. This work is first defining security threats to Olympic Games to than do a historical literature review and a review on potential risks developed in context of similar events with a hermeneutic approach. By this an overview on security threats to Olympic Games in past and present and a non-exhaustive overview on potential security threats to events in future is presented. After this four groups, the Games Family, the Organising Committee, Spectators and Host City / Country, are developed to describe the potential threatened parties. Possible threats are than grouped by their origin in security threats by constructions and environment, security threat emerging out of situations and intentional created security threats. In a last step of analysis possible causes for the formation of security threats within the three groups are described. The paper concludes that Olympic Games have a high potential for security threats, also due to the nature of the Olympic Movement. But also in other events security is a key part of planning and implementing events. This paper is just a scratch on the surface of security as the whole topic is very complex.
Keywords: Olympic games - Security; Ολυμπιακά αθλήματα - Ασφάλεια; Olympic events; Security; Olympic movement; Olympic values; Ολυμπιακά γεγονότα; Ασφάλεια; Ολυμπιακό κίνημα; Ολυμπιακές αξίες